Studies on the activity of phosphotungstic acid (HPW) supported on porous kaolin and effects on the catalytic activity - Mohd. Basir, Norsahika (2015)
Kaolin is an abundant clay mineral and chemically natural hydrous aluminosilicate with the 1:1 type layered structure. In this work mesoporous material derived from raw kaolin was obtained using starch as organic template. The surface area of the kaolin derived porous clay heterostructure (PCH) has increased remarkably from 15 to 756 m2g-1 with pore volume of 0.65cm3g-1. The FTIR spectra after pyridine adsorption showed that both raw kaolin and PCH was synthesized by a wet impregnation method. HPW incorporated into PCH significantly increased the surface acidity by forming mainly Bronsted acidities in acylation of anisole is demonstrated by varying the amount of Lewis and Bronsted acid sites.